Up-Regulation of Immune Checkpoints in the Thymus of PRRSV-1-Infected Piglets in a Virulence-Dependent Fashion - Ruedas-Torres, Inés; Rodríguez-Gómez, Irene M.; Sánchez-Carvajal, José María; Guil-Luna, Silvia; Larenas-Muñoz, Fernanda; Pallarés, Francisco J.; Carrasco, Librado; Gómez-Laguna, Jaime (Frontiers in Immunology, 2021)
Virulent porcine reproductive and respiratory syndrome virus (PRRSV) strains, such as the Lena strain, have demonstrated a higher thymus tropism than low virulent strains. Virulent PRRSV strains lead to severe thymus atrophy, which could be related to marked immune dysregulation. Impairment of T-cell functions through immune checkpoints has been postulated as a strategy executed by PRRSV to subvert the immune response, however, its role in the thymus, a primary lymphoid organ, has not been studied yet. Therefore, the goal of this study was to evaluate the expression of selected immune checkpoints (PD1/PDL1, CTLA4, TIM3, LAG3, CD200R1 and IDO1) in the thymus of piglets infected with two different PRRSV-1 strains. Thymus samples from piglets infected with the low virulent 3249 strain, the virulent Lena strain and mock-infected were collected at 1, 3, 6, 8 and 13 days post-infection (dpi) to analyze PRRSV viral load, relative quantification and immunohistochemical staining of immune checkpoints. PD1/PDL1, CTLA4, TIM3, LAG3 and IDO1 immune checkpoints were significantly up-regulated in the thymus of PRRSV infected piglets, especially in those infected with the virulent Lena strain from 6 dpi onwards. This up-regulation was associated with disease progression, high viral load and cell death. Co-expression of these molecules can affect T-cell development, maturation and selection, negatively regulating the host immune response against PRRSV.